Multiple initiators and C/EBP binding sites are involved in transcription from the TATA-less rat XDH/XO basal promoter. - Chow, C W (1995)
In the present study, we have explored further the organization of the TATA-less rat xanthine dehydrogenase/oxidase gene (XDH/XO). A DNase I hypersensitive site has been identified which it colocalizes with the basal promoter reported previously [Chow et al. (1994) Nucleic Acids Res., 22, 1846-1854]. Gel mobility shift assays indicate the presence of multiple binding factors located in the promoter. At least six footprints were detected of which two have been shown to be C/EBP binding sites. Members of the C/EBP-alpha and C/EBP-beta, but not C/EBP-delta, family are able to bind to these two sites. Deletional and mutational studies revealed that C/EBP binding is not essential for the basal level of transcription initiation of this promoter. Much of the transcriptional activity resides in the -102 to -7 DNA fragment, which contains all initiator activity which acts unidirectionally. Within this fragment, four putative initiator elements could be identified; interestingly, the linear integrity of these initiators is important for efficient transcription of the XDH/XO gene. Separation of the initiators leads to a complete loss of transcription activity; however, this loss could be partially restored by the introduction of an Sp1 binding site upstream of the separated initiators. Despite a difference in usage/frequency of initiation at the various initiators, primer extension analyses reveal similar positions for transcription initiations in both XDH/XO reporter constructs and in the endogenous XDH/XO gene. The differential usage of initiators may imply a possible post-transcriptional regulation for the XDH/XO gene.